2017
DOI: 10.7150/ijbs.16635
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel human long non-coding RNA that regulates hepatic lipid metabolism by inhibiting SREBP-1c

Abstract: Sterol regulatory element binding proteins (SREBPs) are master regulators of hepatic lipid homeostasis. Aberrant expression of SREBPs frequently leads to lipid metabolism dysregulation. Long non-coding RNAs (lncRNAs) have been identified with diverse biological functions, but the effects of lncRNAs on lipid metabolism are rarely reported. Here, we identified a novel human specific lncRNA, lncHR1, as a negative regulator of SREBP-1c expression. Overexpression of lncHR1 inhibited expression of SREBP-1c and fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 30 publications
0
67
0
Order By: Relevance
“…Mechanistically, lncHR1 regulates hepatic lipid metabolism by suppressing SREBP1c promoter activity and negatively regulating SREBP1c and FAS expression. 34 …”
Section: Lncrnas In Hepatic Lipid and Glucose Metabolismmentioning
confidence: 99%
“…Mechanistically, lncHR1 regulates hepatic lipid metabolism by suppressing SREBP1c promoter activity and negatively regulating SREBP1c and FAS expression. 34 …”
Section: Lncrnas In Hepatic Lipid and Glucose Metabolismmentioning
confidence: 99%
“…Overexpression of lncHR1 in mice decreased the expression of SREBP-1c and reduced hepatic and circulating triglyceride levels. However, whether lncHR1 exerts its effects upon the SREBP-1c promoter by direct binding to the DNA or through secondary mediators remains to be clarified [29]. The mechanism by which another hepatic lncRNA, LeXis, represses the expression of cholesterol biosynthetic genes in the liver is better understood.…”
Section: Long Noncoding Rnas Regulating the Sterol Regulatory Elementmentioning
confidence: 99%
“…Elevated triglyceride levels in the circulation are associated with metabolic syndrome and cardiovascular disease [43]. LncRNAs regulating the synthesis and clearance of triglycerides are thus of interest for the generation of novel therapeutic approaches to treat dyslipidemias [29]. …”
Section: Long Non-coding Rnas Regulating Triglyceride Metabolismmentioning
confidence: 99%
“…However, LncRNAs have diverse mechanisms of action, and most of them still need to be further explored [17].There have been many reports showed that many LncRNAs are involved in the occurrence and development of diabetes and the regulation of lipid metabolism, with different mechanisms [18,19].…”
Section: Introductionmentioning
confidence: 99%